The Incomplete Linguistic Features and Schematic Structure in EFL University Students’ Narrative Texts - Tengku Thyrhaya Zein; T. Silvana Sinar; Nurlela Nurlela; Muhammad Yusuf (JETL (Journal of Education, Teaching and Learning), 2019)
This study attempts to investigate the incomplete linguistic features and schematic structure in university students’ narrative text. Qualitative content analysis method was utilized as the research design. The instrument of the research is the writing sheet. The data were taken from a narrative text written by 34 university students of second-year English education study program under the theme of folktales from North Sumatera. The data were analyzed by using the transitivity system to identify linguistic features in narrative text. The findings present that there are 4 different titles of folktales found in the data. From the data, it was commonly found that there is an incomplete part of the schematic structure of narrative text written by students namely complication, evaluation, resolution, and coda. In terms of linguistic features, it is discovered that most of the students have difficulties in differing the tense used covering the use of regular and irregular verbs, and the absence of dialogue. Then, the conclusion can be drawn that the incomplete schematic structure and linguistic features exist in university students’ narrative text. It is also suggested that students keep practicing to write and lecturers should devote higher attention in teaching this genre so that it is able to be comprehended and properly produced by students.